Assessing Variations in Juvenile Court Processing in Urban Versus Rural Courts: Revisiting “Justice by Geography” - Pupo, Jhon A. (Youth violence and juvenile justice, 2021)
Drawing on Feld’s (1991) “justice by geography” thesis, we examined whether juvenile court outcomes and case-level influences on those outcomes varied across urban and rural courts. Using a sample of 60,068 juvenile referrals across 66 counties in one state, we estimated direct effects of urbanism on detention, petition, adjudication, and judicial placement, as well as cross-level interactions between urbanism and several case-level factors for each outcome. We found limited support for the hypotheses. First, findings indicated that odds of detention were significantly greater in more urban courts, but indicated no differences in other outcomes. Second, findings also indicated greater extralegal differences (race, sex, and age) in more urban courts—contrary to hypotheses. Taken together, findings highlight the localized yet complex nature of juvenile justice processing and emphasize the need for additional multilevel research assessing the role of other contextual factors as potential sources of variation across macrosocial units.